PTH-022 Hyperamylasaemia post antegrade double balloon enteroscopy – does indomethacin make a difference?. (8th June 2018) - Zammit, Stefania Chetcuti; Raju, Suneil A; Ching, Hey-Long; Sanders, David S; Sidhu, Reena
Abstract : Introduction: High amylase does not always signify acute pancreatitis and it can occur due to focal areas of ischaemia in the pancreas due to mechanical stress during double balloon enteroscopy (DBE). The use of rectal NSAIDs to prevent post DBE pancreatitis has never been explored unlike in ERCP where patients receiving rectal NSAIDs have a lower incidence of pancreatitis. Methods: Patients who received rectal indomethacin (100 mg) 30 min prior to antegrade DBE were compared to a control group who did not receive indomethacin before the above protocol was implemented. Serum amylase and CRP 3 hours before and after DBE were compared. Results: 240 patients (56 indomethacin, 184 controls; 50% males; mean age 58.5±SD14.0) were included. Indications included: IDA (37.5%), obscure overt gastrointestinal bleeding (17.1%), suspected crohn's disease and strictures (17.9%), complication of coeliac disease (1.3%), small bowel (SB) tumours/polyps (17.9%), others (8.3%). Patients had a median of 13.0±SD13.0 passes, 65.0±SD25.0 min, 170±SD52.0 cm of SB examined. 36.3% underwent a therapeutic procedure during DBE: APC/adrenaline/clips (27.5%), foreign body removal (0.4%), polypectomy (8.3%). Only 4 (1.67%; 2 females) patients developed pancreatitis, all prior to implementation of indomethacin into the local protocol. They had a median age of 47.0±SD3.20 years, 11±SD29.4 passes, 90±SD52.0 min, 150 cm ±SD64.2 cm of SB examined and median hospital stay of 14±SD3.70 days. 3 had polypectomies. 2 episodes occurred in the same patient. All had evidence of pancreatitis on CT scan. None of the patients received indomethacin before DBE. Mean amylase (51.6±SD22.7 vs 143.0±SD143.9 IU/L p=0.0001) and CRP (13.0±SD46.1 vs 17.3±SD81.7 mg/L p=0.0001) after the procedure were significantly higher than before the procedure. Females had a significantly higher amylase than males post procedure (155.2 vs 130.7 IU/L p=0.017). Mean amylase 3 hours after DBE was significantly lower in patients who received indomethacin (114 vs 152) (p=0.044). 83.9% had a rise in amylase in the indomethacin group compared to 92.2% controls.(p=0.064). Whilst there was no correlation between post-procedure amylase (p=0.552), CRP (p=0.058) and duration of the procedure, there was a significant association between amylase post procedure and length of SB examined.(Spearman's rho 0.186; p=0.005) Conclusions: This study identifies a role for rectal indomethacin in patients undergoing antegrade DBE. We have demonstrated that rectal indomethacin reduces amylase post DBE and no patients given indomethacin experienced pancreatitis. Larger studies are required to assess if this also transforms into lowering risk or severity of pancreatitis.